2017
DOI: 10.1186/s12882-017-0592-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary TIMP-2 and IGFBP7 for the prediction of acute kidney injury following cardiac surgery

Abstract: BackgroundAcute kidney injury (AKI) following cardiac surgery is common and associated with poor patient outcomes. Early risk assessment for development of AKI remains a challenge. The combination of urinary tissue inhibitor of metalloproteinase 2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7) has been shown to be an excellent predictor of AKI following cardiac surgery, but reported studies are for predominately non-Asian populations.MethodsAdult patients were prospectively enrolled at Zhon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…28 18 This 0.3 cutoff was further validated in another cohort of ICU patients and also among adults undergoing cardiac surgery. 14,15,27,29,30 15 If neither the intraoperative nor the early postoperative test is positive (>0.3), the treating clinician may be confident the patients will not develop moderate-severe AKI (the "double-negative" [TIMP-2]•[IGFBP7]). Indeed, the negative predictive value using this sampling strategy in the current study was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…28 18 This 0.3 cutoff was further validated in another cohort of ICU patients and also among adults undergoing cardiac surgery. 14,15,27,29,30 15 If neither the intraoperative nor the early postoperative test is positive (>0.3), the treating clinician may be confident the patients will not develop moderate-severe AKI (the "double-negative" [TIMP-2]•[IGFBP7]). Indeed, the negative predictive value using this sampling strategy in the current study was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, models developed in a cardiac surgery cohort may not work well in general ward patients. 36,37 Critically ill patients have higher AKI event rates than do non-ICU patients and also have unique risk factors. These factors can all affect the performance of any model developed in an ICU setting if applied to general ward patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a variety of results in this regard. In several studies [1416], [TIMP-2]•[IGFBP7] detected elevations at 4 h; in another study, elevations were not detected until the day after surgery [17]. A recent study [18], with the most granular time-course published to date, shows bimodal elevations of [TIMP-2]•[IGFBP7] with the first peak occurring intraoperatively and the second 6 h after ICU admission in patients who developed stages 2/3 AKI.…”
Section: Discussionmentioning
confidence: 99%